Morphological Elements of the Betawi Teenagers - Iskandarsyah Siregar; Samsur Rijal Yahaya (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study focuses on the impact of Betawi Language elements on the morphological characteristics of teenagers in Jakarta. Previous research has highlighted that Morphological Interference is the most common form of interference. Similarly, the investigation within Jakarta's coverage area yielded similar results. The study employs a qualitative methodology, utilizing descriptive analysis techniques while incorporating statistical data for reference purposes. The data analyzed in this research consists of sentences in which the Betawi language interferes, specifically regarding affixation, reduplication, composition, and micronization. The findings reveal the presence of morphological interference in the Betawi language concerning morphological variables related to affixation and reduplication. Specifically, the Betawi language demonstrates interference in morphological variables by attaching prefixes, suffixes, and confixes. Additionally, the study indicates the presence of Betawi language interference in speech morphology through reduplication, particularly dwilingga. However, no instances of Betawi language morphological interference were identified concerning composition and micronization in the speech of teenagers in Jakarta